Socio-demographic factors, dental status, oral health knowledge and attitude, and health-related behaviors in dental visits among 12-year-old Shenzhen adolescents: a multilevel analysis - Jinfeng He; Bo Yuan; Shanyu Zhou; Shuyuan Peng; Ye Xu; He Cai; Li Cheng; Yuehua You; Tao Hu (BMC, 2022)
Abstract Background Dental visits can provide education, prevention and treatment measures for teenagers, and help to form correct oral health knowledge and attitude. The purpose of this study was to evaluate the effects of socio-demographic factors, dental status, oral health literacy, and health-related behaviors on dental visits in early 12-year-old adolescents. Methods 953 subjects aged 12 in Longhua district of Shenzhen were investigated. The questionnaire and clinical examination were applied in schools, and two-level logistic regression models were constructed to interpret the effect of individual and contextual factors on Shenzhen adolescents' dental visits. Results A total of 27.6% of the participants had not been to a dentist. After the multiple factors binary logistic regression analysis, it confirmed that the following variables: Shenzhen Hukou (OR 2.133, 95% CI 1.429-3.185), moderate caries (OR 1.404, 95% CI 1.022-1.928) and severe caries (OR 2.546, 95% CI 1.461-4.437), Angle Class II malocclusion (OR 1.703, 95% CI 1.134-2.556), sometimes or never toothbrushing (OR 2.985, 95% CI 1.491-5.975), dental floss usage (OR 1.829, 95% CI 1.250-2.677), having had a toothache within the last 12 months (OR 1.469, 95% CI 1.086-1.986), high knowledge attitude level (OR 1.570, 95% CI 1.106-2.229), moderate knowledge attitude level (OR 1.534, 95% CI 1.073-2.193), were associated factors for dental visit experience. Conclusions The dental visits of 12-year-old children in Longhua district of Shenzhen is affected by multi-dimensional factors. It is suggested that oral health education should be strengthened, good oral hygiene habits should be cultivated, and the needs and utilization of oral health services for non-Shenzhen Hukou adolescents should be paid attention to, so as to effectively improve the overall oral health level of adolescents.